Evaluasi Kebijakan Perhitungan PPh Orang Pribadi Bagi Suami Isteri yang Memilih untuk Menjalankan Hak dan Kewajiban Perpajakannya Sendiri-Sendiri - Ayu Putri, Renita; M Putranti, Titi (Jurnal Ilmiah Administrasi Publik, 2019)
Provisions related to proportional taxes calculation for married filing jointly have already existed since 2008, according to Income Tax Law article 8 verse 2, which also stated specifically on regulation number Per-30/PJ/2017. However, in its implementation nowadays, these couple taxpayers are less concerned about the regulations, both on choosing to do the separate tax filing and the proportional calculation. The purpose of this research is to conduct in-depth analysis about this phenomenon by evaluating the policies and analyzing the obstacles that might occur. The obstacles of the implementation in this research will be observed based on two sides, which are taxpayers and tax authorities side. The result shows that tax policies regarding separated married filing are less effective and efficient due to the considerable effort from tax authorities side related to the supervision of each wife and husband tax filling.